2018
DOI: 10.1038/s41593-018-0255-5
|View full text |Cite
|
Sign up to set email alerts
|

Natural image and receptive field statistics predict saccade sizes

Abstract: Humans and other primates sample the visual environment using saccadic eye movements that shift a high-resolution fovea towards regions of interest to create a clear perception of a scene across fixations. Many mammals, however, like mice, lack a fovea, which raises the question of why they make saccades. Here, we describe and test the hypothesis that saccades work with the adaptive properties of neural networks. Specifically, we determined the minimum amplitude of saccades in natural scenes necessary to provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
114
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(130 citation statements)
references
References 82 publications
(133 reference statements)
16
114
0
Order By: Relevance
“…Many studies have reported a limited range of infrequent eye movements in head restrained mice [6,25,28,29] , consistent with the idea that eye movements are generally driven by head movement.…”
Section: Coordinated Horizontal Eye Movements Are Primarily Compensatsupporting
confidence: 53%
“…Many studies have reported a limited range of infrequent eye movements in head restrained mice [6,25,28,29] , consistent with the idea that eye movements are generally driven by head movement.…”
Section: Coordinated Horizontal Eye Movements Are Primarily Compensatsupporting
confidence: 53%
“…There is conicting evidence about the role of eye movements in mice. Mice have laterally facing eyes with a large eld of view of approximately 280 • extending in front, above, below, and behind the animal's head (Wagor et al, 1980, Dräger, 1978, Hübener, 2003, Seabrook et al, 2017, Samonds et al, 2018. There is only a narrow binocular eld of approximately 40 50 • overlap.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to humans, mice have no fovea and appear to lack other pronounced retinal specializations for high resolution vision (Dräger andOlsen, 1981, Jeon et al, 1998). Despite this, multiple studies have found that head-restrained mice move their eyes (Sakatani and Isa, 2007, Wang et al, 2015, Samonds et al, 2018, Itokazu et al, 2018, Meyer et al, 2018; these eye movements are rapid and conjugate, i.e. both eyes moving together in the same direction, with an average magnitude of 10 20 • and peak velocities that can reach more than 1000 • /s.…”
Section: Introductionmentioning
confidence: 99%
“…In between saccades, periods of stable gaze, termed fixations, allow the integration of information about stimuli falling on the fovea. Successive saccade-fixation cycles incrementally build a detailed picture of the environment (Gottlieb, Hayhoe, Hikosaka, & Rangel, 2014;Liu, Shen, Olsen, & Ryan, 2017;Samonds, Geisler, & Priebe, 2018;Zimmermann & Lappe, 2016), enacting memory associations of foveated objects, their spatial arrangement, and context. Conversely, saccade target selection can be influenced by expectations derived from these associations (Buschman & Miller, 2007;Frank & Sabatinelli, 2017;Najemnik & Geisler, 2005;Peelen & Kastner, 2014).…”
Section: Introductionmentioning
confidence: 99%